Health on thin ice : methods of giving voice to Swedish citizens in urban planning and design to promote health in a cold climate - Berglund, Lotta; Tossavainen, Mia; Nilsson, Kristina L.; Kostenius, Catrine (Luleå tekniska universitet, Hälsa och rehabilitering, 2013)
In the northern, sub-arctic, regions of the world the climate is cold a substantial part of the year which affecting people's health as low temperatures and darkness stress the body. At the same time the cold climate offers opportunities that can be utilized in an innovative manner, both technically and aesthetically, to develop the winter environment to be attractive and health promoting in outdoor activities.The aim of the study was to develop a methodology for giving voice to citizens to be used in the process of urban planning and design for good health in a cold climate. The qualitative investigations of citizen’s experiences of health promoting aspects included two workshops focused on the following questions; What are your experiences of health and well-being in a cold climate? How can this city be planned to promote health during the winter season? The 53 participants came from two cities in the northern part of Sweden. At Workshop 1 small groups of citizens (5-8) were asked to make a collective collage cutting and pasting images from magazines without talking to each other while soft music was playing in the background.When finished the silence was broken and the participants presented their contributions. At Workshop 2 small groups of citizens (5-8) were given maps of the city with different paths for walking tours aimed to pinpoint areas for improvement. After the walk the group presented their ideas for each other and a number of innovative ideas surfaced.Including citizens in the process of urban planning is not only a good source of ideas and information useful in the planning process but may be an opportunity to strengthen health literacy and healthy behavior. This study may serve as an example of an empowerment - based method including citizens in the process of urban planning and design. Godkänd; 2013; 20130306 (andbra)